Dampak Perkembangan Teknologi terhadap Penggunaan Statistik di Indonesia - Asyifa Choirunnisa (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Statistics related to data, starting from the data collection stage to drawing conclusions on data, is studied in statistics. The concepts in statistics are widely applied in various fields and organizations to help analyze data and inform statistics. In this day and age, technological developments have a big impact on the use of statistics. And the use of statistics can be used in various fields, such as economics, we can determine the country's income per capita. On this occasion, the impact of technological developments on the use of statistics was explained and the use of statistics in Indonesia was explained. The conclusion of this article is that current technological developments have a big impact on the use of statistics in making policies or decisions that can be used in various fields with various methods of collecting and processing data with technology.